TEACHING PRACTICE ANXIETY AND PERFORMANCE OF STUDENT-TEACHERS IN FEDERAL COLLEGES OF EDUCATION IN SOUTH-WEST NIGERIA (2015)
Studies have shown that student-teachers are performing below expectation in the Teaching Practice (TP) exercise; a core aspect of the College of Education (CoE) curriculum. This TP poor performance trend in the CoE has been partly attributed to anxiety among the student-teachers. However, previous studies on TP performance have been limited to impacts of supervision issues, students‟ demographic factors, excess workload, duration of the exercise, planning and preparation problems and incentives-related issues without much consideration for the impact of the students‟ anxiety before and during the exercise. This study, therefore, examined teaching practice anxiety as a correlate of student-teachers‟ performance in the teaching practice in Federal Colleges of Education in South-West, Nigeria. The study adopted the descriptive survey design. Three federal CoE were randomly selected out of the four in the South-West, namely, Federal College of Education (Special) Oyo, Federal College of Education (Technical) Akoka, Lagos and Federal College of Education, Osiele, Abeokuta. The combination of stratified, quota and simple random sampling was used to select 100 final year students each from five schools (Languages, Science, Arts and Social Sciences, Education, and Vocational and Technical Education). Instruments used were: Student Teacher Anxiety Scale (r=0.82) and Student‟s Teaching Practice Assessment Rating (r=0.75). Three research questions were answered and three hypotheses tested at 0.05 level of significance. Descriptive statistics, Pearson product moment correlation and multiple regression were used for data analyses. Teaching practice anxiety had a significant correlation with student teachers‟ performance in teaching practice in Federal Colleges of Education (F(10, 1405)=295.2) and accounted for 17.4% of the variance of teaching practice performance. The sources of anxiety, namely, other student-teachers (β=.603), lesson presentation (β=0.314), class management (β=.277), relating to students (β=.252), teaching confidence (β=.194), content mastery (β=.186) and lesson preparation (β=.107) had significant relative contributions to teaching practice performance, while supervision, teaching as a career choice and fear of being observed did not. Also, anxiety had significant relationship with the indices of teaching practice performance as follows: lesson plan (r = -.105); lesson presentation (r = -.685); communication skills (r = -.214); evaluation skills (r= -.202); class management (r = .153). However, student teacher‟s anxiety during TP has no significant relationship with teachers personality (r = -0.037). Anxiety by student teachers during the teaching practice influenced student-teachers‟ performance in teaching practice in Federal Colleges of Education in South-West. Thus, there is the need for adequate preparation for the students through exposure to micro-teaching and proper orientation on rules and regulations to reduce anxiety and improve performance. Keywords: Teaching practice anxiety, Teaching practice performance, Federal Colleges of Education in South-West Nigeria Word count: 415